Potential Association Between Changes in Microbiota Level and Lung Diseases: A Meta-Analysis - Chai, Lan; Wang, Qi; Si, Caijuan; Gao, Wenyan; Zhang, Lun (Frontiers in Medicine, 2022)
Objective: Lung microbiota are increasingly implicated in multiple types of respiratory diseases. However, no study has drawn a consistent conclusion regarding the relationship between changes in microbial community and lung diseases. This study aimed to verify the association between microbiota levels and lung diseases by performing a meta-analysis. Methods: Literature databases, including PubMed, ISI Web of Science, Embase, Google Scholar, PMC, and CNKI, were used to collect related articles published prior to March 20, 2021. The SMD and its related 95%CIs were calculated using a random-effects model. Subgroup, sensitivity, and publication bias analyses were also conducted. Results: Six studies, comprising of 695 patients with lung diseases and 176 healthy individuals, were included in this meta-analysis. The results indicated that the microbiota level was higher in patients with lung diseases than in healthy individuals (SMD = 0.39, 95% CI = 0.22 - 0.55, I2 = 91.5%, P<0.01). Subgroup analysis based on country demonstrated that the microbiota level was significantly higher in Chinese (SMD =1.90, 95% CI = 0.87-2.93, I2 = 62.3%, P<0.01) and Korean (SMD =0.24, 95% CI = 0.13-0.35, I2 = 78.7%, P <0.01) patients with lung diseases. The microbiota levels of patients with IPF (SMD = 1.40, 95% CI =0.42-2.38, I2 = 97.3%, P =0.005), COPD (SMD = 0.30, 95% CI =0.09-0.50, I2 = 83.9%, P =0.004), and asthma (SMD = 0.19, 95% CI =0.06-0.32, I2 = 69.4%, P =0.004) were significantly higher than those of the healthy group, whereas a lower microbiota level was found in patients with CHP. When the disease sample size was > 50, the microbiota level was significantly increased. Subgroup analysis based on different microbiota genera, indicated that A. baumannii and P. aeruginosa were significantly increased in COPD and asthma diseases. Conclusion: We observed that patients with IPF, COPD, and asthma had a higher microbiota level, whereas patients with CHP had a lower microbiota level compared to the healthy individuals. The levels of A. baumannii and P. aeruginosa were significantly higher in patients with COPD and asthma, and represented potential microbiota markers in the diagnosis and treatment of lung diseases.